A határok kára és haszna - a határokról: általában és a Vajdaság kapcsán - Tóth, József (Közép-Európai Közlemények, 2011)
Now when at least in Europe hope seems to open for the fall of borders or for their substantive and functional shifts it worth to raise some border related questions and try to answer them. -Why are the borders? -Is there a necessity of borders? -How to define a natural border? -Possible borders-types? -What are the advanteges of the borders? -How can we reduce disadvantages of the borders? -What can the future hold? The author seeks answers to the abovementioned questions after reviewing Hungarioan and international border studies and troublesome meditations.